"Le Vice-consul": Specular Writing and Text Destruction - Guijarro García, Rafael (Thélème. Revista Complutense de Estudios Franceses, 2014)
Le Vice-consul (1965) by Marguerite Duras is a narrative text, included in the Indian Cycle, and characterized by a story within the story told by an intradiegetic narrator. In the present essay we will analyze how–through a specular writing which creates a series of formal and thematic correspondences between both stories–this metanarrative blurs the diegetic borders and destroys the conventional structure of the novel.